Insights into the role of electrolytes in slurry performance for photoelectrochemical mechanical polishing of GaN wafers - Yuewen Sun; Zhigang Dong; Jihao Zhang; Jiajian Feng; Renke Kang; Shang Gao (Journal of Materials Research and Technology)
Gallium Nitride (GaN) is the representative material among third-generation semiconductors. Due to its strong chemical stability, the chemical mechanical polishing (CMP) efficiency of GaN is extremely low. Photoelectrochemical mechanical polishing (PECMP) has proven effective for efficient, high-quality GaN polishing. The performance of PECMP depends on the slurry's transmittance, conductivity, and material removal ability. Currently, silica sol is mostly used as the slurry for the fine polishing of semiconductor substrates. To ensure the good electrical conductivity required for slurries, electrolytes are added to the silica sol. However, the reaction process of GaN in the silica sol-electrolyte system under photoelectric fields remains unexplored. This study revealed that when using an alkaline electrolyte, the high concentration of hydroxide ions consumes more holes (h+), resulting in slower etching and oxide layer formation compared to acidic electrolytes. Moreover, the stability of silica sol in the PECMP slurry decreases upon the addition of electrolytes, and further instability is observed with increasing voltage, which leads to particle aggregation. This not only reduces the transmittance of the slurry and slows down the oxidation rate on the wafer surface, but also significantly harms the material removal capability of the abrasives. This research provides a theoretical foundation for the development and optimization of PECMP-specific slurries, accelerating the industrial application of PECMP.